The Mediation Role of Competency in the Influence of Work Environment on Employee Performance - Rahayu, Muji; Kesuma Widhiarti, Chandra; Jaelani, Evan; Soswati Ritonga, Duma (Yayasan Pendidikan Belajar Berdikari, 2026)
This study aims to analyze the role of competence as a mediator variable in the relationship between the work environment and employee performance. The study population included all employees of the Sumedang Regency Civil Service and Human Resources Development Agency (BKSDM). The sampling technique used saturated sampling, so that all 53 respondents were used as research samples. Data collection was carried out by distributing questionnaires to predetermined respondents. The collected data were then analyzed using a mediation analysis method with the Hayes Macro Process approach. The results of the hypothesis testing indicate that the work environment and competence have a positive and significant effect on employee performance, both partially and simultaneously. In addition, the analysis results show that the indirect effect of the work environment on performance through competence is significant and has a larger coefficient than the direct effect. These findings prove that competence plays a significant role as a mediator, so that a conducive work environment can optimally improve employee performance.